Analisis Kemampuan Menggunakan Teks Bahasa Baku Berdasarkan Kaidah Ejaan Bahasa Indonesia (EBI) oleh Siswa Kelas X SMK Swasta Jambi Medan - Elisa Permata Sari; Rosmawati Harahap (LPPM STIKes SITI HAJAR dan Insight Power, 2021)
The research was carried out with the aim of describing the mastery, application, and use of Indonesian Spelling in standard language texts based on EBI rules by students of class X TKJ-1 SMK Swasta Jambi Medan in Academic Year 2021-2022. This study used a quantitative descriptive method with a population of 145 people and a sample of 37 people. The total sample is 25% of the total population. The score of the highest student is equal to 85 while the lowest score is 60. Based on the results of data analysis, the average mastery, application, and use of EBI by students class X TKJ-1is equal to 66.62 (30%) which is categorized as